ECG Analysis and Arrhythmia Classification using Narrowband Frequency Signal (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Electrocardiogram (ECG), a non invasive technique plays a crucial function in communication part and as well as in signal processing. A methodology used to diagnose cardiovascular diseases with the help of narrowband frequency signals has been proposed. An ECG signal provides useful information about electrophysiology of heart rhythm and diagnose the disease.  ECG signals are contaminated under the help of Power Line Interference (PLI) and also bioelectric signals. It provides valuable results of heart disease and cardio vascular system. It is complicated by process raw cardiogram signal in PLI. This can be overcome by the technique known as Ramanujan periodic transform (RPT) with some noise in result. In this proposed work, the noise is reduced by exploitation QRS detection algorithm and arrhythmia classification. The noise is detected by calculating the summation (E) of Euclidean error in each and every back (G) in filter based techniques.